2013
DOI: 10.1007/s10120-013-0248-8
|View full text |Cite
|
Sign up to set email alerts
|

Low ING4 protein expression detected by paraffin-section immunohistochemistry is associated with poor prognosis in untreated patients with gastrointestinal stromal tumors

Abstract: Background Inhibitor of growth 4 (ING4) has deserved attention as a tumor suppressor gene in many malignant tumors. In our study, we investigated ING4 immunoexpression in gastrointestinal stromal tumors (GISTs) and its prognostic value. Method The expression of ING4 and Ki67 was investigated in 41 samples of various risk gastrointestinal stromal tumors by immunohistochemical technique. The associations of ING4 expression and clinicopathological parameters, and prognosis of the patients, were analyzed by multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The reduced expression of tumor suppressor ING4 has been reported in various malignancies, and down-regulation of ING4 is correlated with increased tumor metastasis, advanced TMN stages and poor patients survival in melanoma [18], gastric cancer [19] and breast cancer [20]. In the present study, we showed that both ING4 mRNA and protein expressions were lower in CRC tissues when compared with paired normal colon tissues.…”
Section: Discussionsupporting
confidence: 61%
“…The reduced expression of tumor suppressor ING4 has been reported in various malignancies, and down-regulation of ING4 is correlated with increased tumor metastasis, advanced TMN stages and poor patients survival in melanoma [18], gastric cancer [19] and breast cancer [20]. In the present study, we showed that both ING4 mRNA and protein expressions were lower in CRC tissues when compared with paired normal colon tissues.…”
Section: Discussionsupporting
confidence: 61%
“…The clinicopathological features [age, gender, risk group, mitotic count in 50 high power fields (HPFs), tumor size, tumor location, growth pattern, cellularity, nuclear pleomorphism, ulceration, hemorrhage, necrosis, cell type, surgical/biopsy procedure type, and ki-67 proliferation index] were achieved from the original pathology reports. risk-groups had been established and adopted according to the criteria of Fletcher et al (16) based on tumor size and mitotic count in 50 HPFs. In the present study, the cases were divided into two groups as the "lower-risk group" and "high-risk group" to predict the prognosis of GISTs.…”
Section: Methodsmentioning
confidence: 99%
“…ING4 is mainly lost or downregulated at the RNA level in human cancers. These include astrocytic tumors of the central nervous system [171,172], breast cancer [75,168,173–175], malignancies of the gastrointestinal tract [176–178], HNSCC [179,180], HCC [181,182], melanoma [75,183], lung [75], ovarian [75] and prostate cancer [75]. Like ING1 [80], ING4 downregulation correlates with higher WHO grades of malignancy in astrocytoma [172], with unfavorable prognosis of breast cancer patients [89,173,184] and with angiogenesis in multiple cancer types [106,184–190] and other diseases [191].…”
Section: Almost Two Decades Of Learning: From Candidate Tumor Suppresmentioning
confidence: 99%